The biogenesis of E. coli inner membrane proteins - Luirink, Joen (Henry Stewart Talks, 2007)
SRP-mediated targeting to the inner membrane, Structure and function of the Sec-translocon in membrane insertion, Role of YidC as an insertase and membrane chaperone
Archived at 2020/08/13